2019
DOI: 10.1080/25785826.2019.1605036
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter, observational clinical study of abatacept in Japanese patients with rheumatoid arthritis

Abstract: The aim of this study was to assess abatacept in rheumatoid arthritis (RA) patient. Patients (20 men, 89 women, aged 61.9 ± 10.4 y) who responded inadequately to conventional synthetic disease-modifying anti-rheumatic drug were treated with abatacept for 24-months. Disease activity score in 28 joints (DAS28-CRP) was evaluated. Of 109 patients, 82 (75.2%) were on methotrexate (MTX; mean dosage 9.0 ± 2.7 mg/week); 48 (44.0%) were naive to biologics and 61 (56.0%) had failed biologics. The 1-and 2-year retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…As previously reported with abatacept [ 10 , 25 , 26 , 36 ] and other bDMARDs [ 37 , 38 ], the clinical outcomes reported here were higher in biologic-naïve patients than in those with failure of prior biologic treatments and may suggest a greater benefit of earlier treatment [ 4 ]. The results from a study with tocilizumab showed equal efficacy in biologic-naïve patients as those with 1 or 2 previous bDMARD failures; however, overall treatment effectiveness was lower in those with > 2 failures [ 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…As previously reported with abatacept [ 10 , 25 , 26 , 36 ] and other bDMARDs [ 37 , 38 ], the clinical outcomes reported here were higher in biologic-naïve patients than in those with failure of prior biologic treatments and may suggest a greater benefit of earlier treatment [ 4 ]. The results from a study with tocilizumab showed equal efficacy in biologic-naïve patients as those with 1 or 2 previous bDMARD failures; however, overall treatment effectiveness was lower in those with > 2 failures [ 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, in other studies, infections were the second reported AEs for GOL and the most frequent AE for ABT [76,77]. Regarding skin disorders, it is well known that anti-TNFα drugs play a role in the onset of dermatological manifestations, including urticaria, erythema and dermatitis, with a frequency ranging between 10-60% [78,79].…”
Section: Discussionmentioning
confidence: 92%
“…Nonetheless, disease activity was significantly reduced in the AO group; notably, steroid dose was also reduced in a manner similar to that observed in the AY group. Unlike the synergistic effects of tumor necrosis factor inhibitors, the efficacy of abatacept is not substantially enhanced when it is administered in combination with MTX [29][30][31][32][33]. Of note, there appears to be a benefit of MTX in combination with abatacept for patients with greater disease activity or during long-term treatment [34][35][36].…”
Section: Discussionmentioning
confidence: 99%